“Estudio de la fertilización edáfica en cultivo establecido de banano en la Hacienda Isabel María” - Vera Arana, Vladimir Alfonso (2018)
SUMMARY ESTUDY OF SOIL FERTILIZATION IN CROP ESTABLISHED BANANA AT THE ISABEL MARIA FARM AUTHOR: Vladimir Alfonso Vera Arana TUTOR: Ing. Agrop. Álvaro Pazmiño Pérez, MsC. The practical component of general examination, was established in December 2018 in the banana farm Isabel Maria, located in the parish of La Union in the Babahoyo city Los Rios province, studied fertilization that is implemented by the producer. The objectives of the project were: 1) Stating the process of fertilization in the established culture of bananas through literary review. 2) Recogniza different ways of fertilization in the cultivation of bananas. 3) To determine the incidence of soil fertilization applied at the hacienda. A field visit to the ranch with the presence of the producer was conducted, determined that the fertilization program is implemented without using soil test and leaf as main guide, without following stipulated by the literature. To improve the case it is proposed to establish a program of fertilization as alternative production technique on the banana farm Isabel Maria.